Kaidah yang Berkaitan dengan Talak - Muhammad Saputra; Muhammad Amar Adly; Heri Firmansyah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The purpose of this study is to explore and understand the various rules of Islamic jurisprudence related to divorce, and how to apply these rules in problems related to divorce. This study uses a library research approach. The results of the study indicate that divorce should be imposed based on valid reasons and lead to the need to separate. Imposing divorce without a clear reason can result in sin for the husband. In addition, the valid requirements for divorce are that the husband who makes it must be mature and of sound mind, so that he can be responsible for the decision. This study examines four main rules of Islamic jurisprudence related to the law of divorce in Islam, namely: first, divorce cannot be separated and falls according to the number mentioned, second, the place where the divorce falls is where the marriage bond occurs, third, the law of divorce follows the nature that is coupled with the number so that the number of divorces is in accordance with what is mentioned, and fourth, even though divorce is said to be related to the past, the law of its fall still applies when the words are pronounced as well as examples and exceptions. This study uses a literature study method with analysis of the Qur'an, Hadith, and the opinions of classical and contemporary scholars. The results of the study confirm that these rules are very important in determining the validity, time of divorce, and its legal implications, thus providing legal certainty for married couples in Islamic households. The purpose of this study is to explore and understand the various Islamic jurisprudence rules related to divorce, as well as how to apply these rules in problems related to divorce. This study also aims to analyze the relevance and legal implications of these rules in the practice of Islamic family law, in order to provide a comprehensive understanding and legal certainty for Muslims in living their household life.